Low levels of morning salivary α-amylase activity predict higher number of depressive symptoms in a community sample of children - Maldonado Montero, Enrique Francisco; Fernández Martín, María Eugenia; Trianes Torres, María Victoria; Ortiz García, Carmen; Engüix, Alfredo; Nislin, Mari (Anales de Psicología / Annals of Psychology, 2018)
Models of the etiology of depressive disorders suggest that the onset of a depressive episode is the result of a complex phenomenon based on the interaction between genetic background, critical environmental factors such as life stressors and traumatic events, and the effects of neuroendocrine changes associated with the stress response. Numerous studies have highlighted the usefulness of morning cortisol (C) as a potential predictor of depressive episodes. The aim of this study was to compare the effectiveness of C, salivary alpha-amylase (sAA) activity/output, and the sAA/C ratio in predicting depressive symptoms in a community sample of 99 children aged 8-11 years old. Two saliva samples were obtained in the morning on two different school days. Teachers described their pupils’ behavior by using the internalizing problems scales of the Teacher’s Report Form (TRF) questionnaire. Our results indicate that, regardless of gender, the best predictor of depressive/withdrawal scores and overall internalizing scores on the TRF was lower mean morning levels of sAA activity. Hence, sAA could be proposed as a biological marker for the risk of developing a first episode of depressive illness in child samples.